Enhanced Vasoconstriction Mediated by α1-Adrenergic Mechanisms in Small Femoral Arteries in Newborn Llama and Sheep Gestated at Low and High Altitudes - Moraga, Fernando A.; Reyes, Roberto V.; Ebensperger, Germán; López, Vasthi; Llanos, Aníbal J. (Frontiers in Physiology, 2021)
We previously demonstrated that newborn llama (NBLL) express high levels of α1 adrenergic receptors, which provide a potent vasoconstriction response compared to newborn sheep (NBSH) gestated at sea level. However, data regarding the impact of chronic gestational hypobaric hypoxia on α-adrenergic vasoconstriction in the neonatal life has not been studied. We evaluated if gestation under chronic hypobaric hypoxia modifies α1-adrenergic vasoconstrictor function in NBLL and NBSH. We compared the vasoconstrictor response induced by potassium and α-adrenergic stimuli in isolated small femoral arteries of NBLL and NBSH gestated at high altitude (HA, 3,600 m) or low altitude (LA, 580 m). The maximal contraction (RMAX) and potency (EC50) to potassium, NA, and PHE were larger in HA than LA-NBLL. RMAX to potassium, noradrenaline (NA), and phenylephrine (PHE) were lower in HA compared to LA-NBSH and potency results were similar. Competitive blockade with prazosin showed that RNLL LA/HA have a similar pA2. In contrast, NBSH increased pA2 values in HA compared to LA. Finally, small femoral arteries denudated or treated with LNAME in LA and HA lacked NO or endothelium participation in response to PHE stimulation. In contrast, NBSH displayed that denudation or blockade with LNAME support NO or endothelium participation in response to PHE activation. In conclusion, HA chronic hypoxia enhances α1 adrenergic receptor activity in small femoral arteries in NBLL, to a higher degree than NBSH, implying a higher vasoconstriction function.